Parliamentary clashes, protestant foundations: the ‘British and Foreign Anti-Slavery Society’ and mid-nineteenth-century British abolitionism (Ágora Journal, 2026)
In 1839, the British and Foreign Anti-Slavery Society (BFASS) was founded in England as a non-governmental abolitionist organization whose aim was to weaken the system of slavery in various regions of the world. Currently recognized as one of the earliest institutions devoted to the defense of human rights, the BFASS originated in the Protestant tradition of the Society of Friends and, for decades, upheld abolitionist positions that often diverged from the policies adopted by the British government. This article seeks not only to trace the Society’s trajectory but also to demonstrate that the abolitionism of its members went beyond humanitarian concerns, revealing the political and economic tensions of mid-nineteenth-century England as well.
Keywords: Abolitionism; England; 19th century